2015
DOI: 10.1093/europace/euv057
|View full text |Cite
|
Sign up to set email alerts
|

EFFICAS II: optimization of catheter contact force improves outcome of pulmonary vein isolation for paroxysmal atrial fibrillation

Abstract: AimsA challenge of pulmonary vein isolation (PVI) in catheter ablation for paroxysmal atrial fibrillation (PAF) is electrical reconnection of the PV. EFFICAS I showed correlation between contact force (CF) parameters and PV durable isolation but no prospective evaluation was made. EFFICAS II was a multicentre study to prospectively assess the impact of CF guidance for an effective reduction of PVI gaps.Methods and resultsPulmonary vein isolation using a radiofrequency (RF) ablation catheter with an integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
300
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 344 publications
(316 citation statements)
references
References 24 publications
10
300
3
3
Order By: Relevance
“…The recommendations of CF parameters in PVI procedures include a target average CF value of 10-30 g and a minimum FTI value of 400 g for each RF lesion. 5,14,15 Another landmark study, TOCCASTAR by Reddy et al, confirmed the importance of using CF-guided strategies in meeting primary safety and effectiveness endpoints in PVI ablation procedures. 16 In results published by Neuzil et al, 10 evidence has been offered that supports the concept that an LSI of greater than 5 predicts reconnection risk in PVI ablation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The recommendations of CF parameters in PVI procedures include a target average CF value of 10-30 g and a minimum FTI value of 400 g for each RF lesion. 5,14,15 Another landmark study, TOCCASTAR by Reddy et al, confirmed the importance of using CF-guided strategies in meeting primary safety and effectiveness endpoints in PVI ablation procedures. 16 In results published by Neuzil et al, 10 evidence has been offered that supports the concept that an LSI of greater than 5 predicts reconnection risk in PVI ablation.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, an FTI Z400 g/s has been suggested as a surrogate end-point to predict the creation of transmural lesions in RF. 5,6 Booth et al recently highlighted the new real-time CF parameter of lesion size index (LSI). This novel parameter incorporates RF power, ablation duration, and CF in a dimensionless ratio independent of traditional parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Six (5%) of the 124 patients withdrew their consent during follow-up and were excluded from the study, resulting in a total of 118 Duration of AF, mo 12 [7,24] 12 [7,24] 12 [7,24] Type of AF Persistent 69 (59) 35 (57) 34 (60) Long-standing persistent 49 (42) 26 (43) 23 (40) CAD 11 (9) 5 (8) 6 (11) Valvular disease 14 (12) 8 (13) 6 (11) Hypertension 64 (54) 35 (57) 29 (51) Diabetes mellitus 9 (8) 5 (8) 4 (7) CHADS 2 score (87) 52 (85) 51 (90) 2-3 14 (12) 8 (13) 6 (11) Values are mean±SD, median [first quartile, third quartile], or n (%). AF indicates atrial fibrillation; BMI, body mass index; CAD, coronary artery disease; CHADS 2 , stroke risk score based on congestive heart failure, hypertension, age ≥75 years, diabetes mellitus, prior stroke/transient ischemic attack/thromboembolism; CHA 2 DS 2 -VASc, stroke risk score based on congestive heart failure, hypertension, age ≥75 years, diabetes mellitus, prior stroke/ transient ischemic attack/thromboembolism, vascular disease, age 65-74 years, sex; LA, left atrium; and LVEF, left ventricular ejection fraction.…”
Section: Patientsmentioning
confidence: 99%
“…Contact force-sensing catheters were not used. The EFFICAS I and II studies (TactiCath Prospective Effectiveness) have shown a reduction in gap formation around the PVs when ablation was guided by contact force sensing, 23,24 but, to date, a randomized controlled trial showing better clinical outcomes associated with contact force-guided ablation is lacking. Follow-up did not use loop recorder systems.…”
Section: Fink Et Al Catheter Ablation Strategies For Persistent Af LImentioning
confidence: 99%
“…Ablation was performed where the atrial myocardium connects to the PV sleeve, and typically with a >2 cm distance between the ablated anterior and posterior carina. Lesions were closely spaced: an ILD max ≤6 mm, based on previous study findings 20,22,23 and energy (35 W) was delivered to reach a minimal AI ≥400 at the posterior wall and ≥550…”
Section: Towards a Standardised Protocol For Durable Pvi: The Close Pmentioning
confidence: 99%